Analisis Maqashid al-Khamsah Pada Pengharaman Riba - Haniifatuz Zahira Yanadewi; Solahuddin Al- Ayubi (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2024)
This study aims to analyse the maqasid of sharia on the prohibition of usury. This research method uses library research by providing analysis and conclusions on the prohibition of riba using the maqashid al-khamsah approach. The results of this study show that the maqasid of sharia on the prohibition of riba can be protected in five aspects. Among other things, the hifz al-din (protecting religion) aspect of the prohibition of riba seeks to protect Muslims from economic practices that can damage the integrity of religion and violate Islamic ethical values. The hifz al-nafs (protecting the soul) aspect of the prohibition of riba underscores Islam's role in eliminating individualism, malice, and hatred, as well as creating an economic environment that supports the well-being of the individual's soul. The hifz al-'aql (protecting reason) aspect of the prohibition of riba seeks to create an environment that promotes the clarity of mind and mental well-being of Muslims. The hifz al-nasl (protecting offspring) aspect of the prohibition of usury seeks to create a healthy economic environment where families can manage their finances without being burdened by interest debts that can harm offspring. The hifz al-mal (protecting property) aspect of the prohibition of usury eliminates injustice, oppression, and social suffering, prevents usury from being receivable, encourages participation and increases employment, and avoids a catastrophic financial crisis. Thus, it can maintain sustainability and fairness in the maintenance of property.